2010
DOI: 10.1111/j.1600-0625.2010.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐renewal capacity of human epidermal Langerhans cells: observations made on a composite tissue allograft

Abstract: :  Epidermal Langerhans cells (LC) are dendritic, antigen‐presenting cells residing within mammalian epidermis and mucosal epithelia. When massively depleted, they are replaced by cells of bone‐marrow origin. However, their renewal within normal skin under steady‐state conditions is not precisely known. We observed that epidermal LC within a human hand allograft remain stable in the long term (10 years) and are not replaced by cells of recipient’s origin; furthermore, we observed a Langerhans cell in mitosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 12 publications
8
53
0
Order By: Relevance
“…[2][3][4] Observations in humans also confirm that LCs can be self-maintained [5][6][7] or replaced by bone marrow-derived cells in the context of transplantation and inflammation. [7][8][9][10] The nature of bone marrow-derived LC precursors that repopulate the epidermis after inflammation is incompletely defined. Experiments in mice with clodronate depletion and bead-labeling suggest a monocyte origin but do not completely exclude other precursors.…”
Section: Introductionmentioning
confidence: 75%
“…[2][3][4] Observations in humans also confirm that LCs can be self-maintained [5][6][7] or replaced by bone marrow-derived cells in the context of transplantation and inflammation. [7][8][9][10] The nature of bone marrow-derived LC precursors that repopulate the epidermis after inflammation is incompletely defined. Experiments in mice with clodronate depletion and bead-labeling suggest a monocyte origin but do not completely exclude other precursors.…”
Section: Introductionmentioning
confidence: 75%
“…18,41 Under inflammatory conditions, different murine models show different results and show that LCs can have a dual origin, both from local proliferation and from blood progenitors. 7,8,16,37,42 …”
Section: Discussionmentioning
confidence: 99%
“…16,17 In particular, blood CD1a 1 CD11c 1 cells were shown to express high CD1c (BDCA-1) levels and to rapidly acquire a LC phenotype. 17 After transplantation, LCs of donor origin have been observed in the skin of the host for up to 10 years, 18 suggesting the presence of a local precursor that remains to be identified. However, the pathways leading to LC differentiation during inflammation are still poorly defined, both in terms of differentiation factors and of possible LC precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are then replaced by long-term LCs arising from the self-renewing precursors described above (9). In humans, convincing evidence that the LC network is reconstituted through proliferation of epithelium-residing precursors has come from stem cells (10,11) or solid organ transplantation (12,13). Indeed, it has been shown that skin LCs in grafted hand from distinct patients were still from donor origin .10 y after transplantation (12,13).…”
mentioning
confidence: 99%
“…In humans, convincing evidence that the LC network is reconstituted through proliferation of epithelium-residing precursors has come from stem cells (10,11) or solid organ transplantation (12,13). Indeed, it has been shown that skin LCs in grafted hand from distinct patients were still from donor origin .10 y after transplantation (12,13). However, the use of immunosuppressive drugs in that context may not allow stating that a tolerated graft recapitulates the steady-state with regard to their deleterious effects on monocyte circulation and differentiation in vitro as well as in vivo (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%